INTERNALISASI NILAI PANCASILA TERHADAP GENERASI MUDA SEBAGAI WUJUD MEMPERTAHANKAN BUDAYA BANGSA - Mujahidah, Idah; Dewi, Dinie Anggraeni (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This article contains an idea how to internalize the values of Pancasila to the younger generation in the era of globalization. This idea was created to respond to the changes that have emerged in the community, especially the environment of the younger generation as a result of globalization, where these changes have an impact on various things, one of which is the erosion of the nation's culture as a result of cultural influences from outside. This article contains several things including, the values of each of the Pancasila precepts, the challenges of Pancasila in the era of globalization, and the internalization of Pancasila values for the younger generation. The method used in this article is to use descriptive qualitative methods through literature studies or literature studies through several sources relevant to related topics. On the other hand, this research also aims to make it easier for readers to understand every meaning contained in Pancasila which is discussed in light and easy to understand language. From this goal, this research is interesting to study because in the end this article also creates a goal to create motivation for the younger generation to be able to practice the values of Pancasila in everyday life as well as be able to avoid the bad changes of this globalization.